Maternal and perinatal outcomes in relation to body mass index - Soma Taher; Chro Najmaddin Fattah (Advanced Medical Journal)
Background and objectives: Maternal obesity has become a global threat and has a major public health burden to the mother and her baby. The prevalence of maternal obesity has risen in the past two decade. The aim of the study is to compare maternal and perinatal outcomes of pregnancy in relation to BMI.